The impact of Holocene deglaciation and glacial dynamics on the landscapes and geomorphology of Potter Peninsula, King George Island (Isla 25 Mayo), NW Antarctic Peninsula - Heredia Barión, Pablo A.; Strelin, Jorge A.; Roberts, Stephen J.; Spiegel, Cornelia; Wacker, Lukas; Niedermann, Samuel; Bentley, Michael J.; Pearson, Emma J.; Czalbowski, Nadia T. Manograsso; Davies, Sarah J.; Schnetger, Bernhard; Grosjean, Martin; et al. (Frontiers in Earth Science, 2023)
The timing and impact of deglaciation and Holocene readvances on the terrestrial continental margins of the Antarctic Peninsula (AP) have been well-studied but are still debated. Potter Peninsula on King George Island (KGI) (Isla 25 de Mayo), South Shetland Islands (SSI), NW Antarctic Peninsula, has a detailed assemblage of glacial landforms and stratigraphic exposures for constraining deglacial landscape development and glacier readvances. We undertook new morphostratigraphic mapping of the deglaciated foreland of the Warszawa Icefield, an outlet of the Bellingshausen (Collins) Ice Cap on Potter Peninsula, using satellite imagery and new lithofacies recognition and interpretations, combined with new chronostratigraphic analysis of stratigraphic sections, lake sediments, and moraine deposits. Results show that the deglaciation on Potter Peninsula began before c. 8.2 ka. Around c. 7.0 ka, the Warszawa Icefield and the marine-facing Fourcade Glacier readvanced across Potter Peninsula and to the outer part of Potter Cove. Evidence of further readvances on Potter Peninsula was absent until the Warszawa Icefield margin was landward of its present position on three occasions: c. 1.7–1.4 ka, after c. 0.7 ka (most likely c. 0.5–0.1 ka), and by 1956 CE. The timing of Holocene deglaciation and glacier fluctuations on Potter Peninsula are broadly coeval with other glacier- and ice-free areas on the SSI and the northern AP and likely driven by interactions between millennial–centennial-scale changes in solar insolation and irradiance, the southern westerlies, and the Southern Annular Mode.